THEORETICAL BASIS OF CHANGE MANAGEMENT IN THE ORGANIZATION - HAVLOVSKA, Nataliia; SEMENCHENKO, Vitaliy; YABLONSKY, Taras; HYMENNA, Emma (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the existing models of change management, in particular: the model of business transformations by K. Levin, the ADKAR model by D. Hiatt, the McKinsey model, the 8 forces model by J. Kotter, theory E and theory O, the iceberg model of change management by V. Kruger, the transition model of V. Bridges. K. Levin’s business transformation model is one of the most popular and successful change management models and includes 3 stages of the change process, namely: 1) (unfreezing, 2) changes, 3) freezing. ADKAR model - author D. Hayatt, includes 5 stages, in particular: 1) awareness - awareness of the need for changes; 2) desire – desire to support and participate in changes; 3) knowledge – knowledge of how to change; 4) ability – the ability to acquire new skills; 5) reinforcement (compensation) – support for the consolidation of changes. The McKinsey 7-S model contains seven interrelated elements: 1) common values, 2) skills, 3) personnel, 4) style, 5) strategy, 6) structure, 7) systems. J. Kotter’s 8 forces model is following: 1) create a sense of urgency, 2) build a governing coalition, 3) create a strategic vision and initiatives, 4) recruit an army of volunteers, 5) activate action by removing barriers, 6) generate short-term victories, 7) sustain achievements, 8) institutionalize changes. E Theory and O Theory of organizational changes by Michael Berr and Nitin Nohria single out two polar concepts of organizational development, each of which defines a corresponding change strategy. E Theory starts from financial goals and focuses on their effective achievement, O Theory considers the organization as a self-developing system and is more focused on the corporate culture, goals and motives of the organization’s employees. The iceberg model of change management, which was proposed by W. Krüger, allows you to form types of change implementation based on the type of changes and the strategy that should be applied. V. Bridges’ model of transition is more focused on transition than on change and consists of 3 stages: 1) ending, loss and letting go of the lost, 2) neutral zone, 3) new beginning. Appropriate conclusions have been drawn.